(untitled) (Research, Society and Development, 2024)
Falls among older adults represent a highly complex public health issue, associated with a substantial increase in morbidity, mortality, and a significant reduction in the quality of life for this vulnerable population. The present study aimed to systematically explore the underlying causes of falls among older adults and discuss the most effective preventive interventions in the current context. A narrative review was conducted, integrating literature data obtained from international databases, considering articles published between 2020 and 2024 and using descriptors such as "falls in older adults," "prevention," and "quality of life." The analysis revealed that falls are mainly due to a complex interplay between intrinsic factors, such as frailty, polypharmacy, cognitive deficits, and sensory impairments, and extrinsic factors, such as unsafe environments and architectural barriers. The most promising interventions were found to be multifactorial, encompassing physical exercise programs focused on muscle strengthening and balance improvement, environmental adaptations, and assistive technologies, with an emphasis on remote monitoring systems and wearable technologies. However, adherence to interventions is hindered by barriers such as resistance to change among older adults and limitations in access to specialized resources. It is concluded that fall prevention requires integrated and individualized approaches that combine physical, environmental, and technological strategies aimed at reducing risks and promoting autonomy and quality of life among older adults.